Viewing the Asian American Experience Through a Culturally Centered Research Lens: Do Scholarship in Family Science and Related Disciplines Fall Short? - Fang, Shi-Ruei Sherry; McDowell, Teresa; Goldfarb, Katia P.; MacDonald, Angella; Perumbilly, Seb; Gonzalez-Kruger, Gloria E. (Marriage & Family Review, 2008)
To better understand and serve Asian-Americans, it is imperative for the family science related fields to take a leadership role in providing in-depth insight into Asian-American families. In this article we report a descriptive analysis of articles published in prominent family-based journals over a 14-year period (1992–2006) relative to their attention to Asian-American families. This study examines the types of research conducted and the knowledge that has been generated about Asian-American families. It also provides a framework for considering future culturally centered research with this population.
_eprint: https://doi.org/10.1080/01494920802185058
Keywords: Asian-Americans; culturally sensitive research approaches; dept.mft; family science; peer-reviewed

Normal Madness, Murder and Mayhem - Lynch, J. Edward (Xlibris Corp, 2008)
Keywords: dept.mft; faculty_collection